Systematic Review on the Role of IL-6 and IL-1β in Cardiovascular Diseases - Katkenov, Nurlubek; Mukhatayev, Zhussipbek; Kozhakhmetov, Samat; Sailybayeva, Aliya; Bekbossynova, Makhabbat; Kushugulova, Almagul (Journal of cardiovascular development and disease, 2024)
Cardiovascular diseases (CVDs) are a leading cause of global morbidity and mortality, significantly driven by chronic inflammation. Interleukin-6 (IL-6) and interleukin-1β (IL-1β) are critical inflammatory cytokines implicated in CVD progression. This systematic review evaluates the roles of IL-6 and IL-1β in CVDs by synthesizing data from relevant studies to understand their impact on cardiovascular outcomes and identify potential therapeutic interventions. A comprehensive literature search was conducted using PubMed and Embase, covering studies from January 2014 to December 2024. Inclusion criteria encompassed studies investigating IL-6 and/or IL-1β in CVDs, including human and relevant animal models, and reporting clinical outcomes, molecular mechanisms, or therapeutic interventions. Data extraction and quality assessment were performed independently by two reviewers. Our review included 12 studies focusing on the roles of IL-6 and IL-1β in various CVDs. Elevated IL-6 levels were significantly associated with peripheral artery disease, myocardial infarction, and heart failure, while IL-1β levels were linked to worse outcomes in coronary artery disease and heart failure. Meta-analyses indicated a significant association between higher IL-6 and IL-1β levels and increased risk of adverse cardiovascular events. These findings suggest that targeting IL-6 and IL-1β could offer promising therapeutic strategies for reducing inflammation and improving cardiovascular outcomes.